An Evidence-Based Update on the Impact of Local Antimicrobials as Adjunct to Periodontal Therapy - Hussein, Nabaz Yahya; Aziz, Sadat Abdulla; M. Ways, Twana Mohammed; Amiri, Omed; Al-Obaidi, Hisham; Ford, Dianne (Kurdistan Journal of Applied Research, 2023)
Local antimicrobials as adjunct to mechanical periodontal therapy have been used widely to enhance the outcome of treatment. However, consensus has yet to be achieved regarding what and how these antimicrobials can be used. Therefore, this narrative review highlights the most common antimicrobials examined and provides an updated analysis of the benefits, limitations, and clinical outcomes associated with use of antimicrobials as adjunct to mechanical periodontal therapy. Based on the evidences gathered, it is clear that combining local antimicrobial agents with scaling and root debridement (SRD) offers significant therapeutic advantages in periodontal therapy and minimizing many side effects linked to systemic antibiotic therapy. Amongst the antimicrobials used, chlorhexidine (CHX) showed the most significant clinical improvement, followed by doxycycline (DOX), tetracycline, and metronidazole (MTZ), all of which helped reduce periodontal bacteria load and improve treatment outcome. CHX demonstrated the greatest clinical improvement due to its broad-spectrum antimicrobial activity, strong substantivity, and its application in sustained-release formulations. DOX followed closely in effectiveness, offering a unique advantage through its dual role as both an antimicrobial and a matrix metalloproteinase inhibitor. Tetracycline, though slightly less effective than DOX, still provided considerable clinical benefits, especially when used in sustained-release systems, despite increasing bacterial resistance in some cases. MTZ showed the lowest clinical improvement among the agents reviewed, but it remains valuable due to its targeted action against anaerobic bacteria, which are prominent in periodontal infections. The findings of this study will help the general practitioners select the most suitable local antimicrobial therapy as adjunct to mechanical periodontal therapy.